Illustrated key to the species in the genus Laminiceps Costa, 1863 (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with descriptions of twelve new species - Brailovsky, Harry; Barrera, Ernesto (Zootaxa, 2023)
The genus Laminiceps Costa, 1863 (Coreidae: Acanthocephalini) is redescribed, and 12 new species are described: L. aburtonia (Brazil), L. curiosus (French Guiana), L. eustoliana (Paraguay), L. excelsus (Peru), L. factiosus (Brazil), L. fundatus (Trinidad), L. gelidus (Brazil), L. genuinus (Peru), L. halatus (Brazil), L. infrequens (Brazil), L. lentus (Venezuela), and L. navus (Bolivia). A revised key to all 30 species is included. Dorsal and lateral photos of all species are provided as well as photos of male genital capsules and parameres where available.